High-pressure emulsion formation in cylindrical coaxial orifices: Influence of cavitation induced pattern on oil drop size. (September 2015) - Schlender, Marc; Spengler, Annkathrin; Schuchmann, Heike P.
Highlights: The influence of cavitation on high pressure emulsion formation is investigated. Three characteristic cavitation patterns downstream of the orifice were found. Transition from jet cavitation to hydraulic flip influence droplet breakup. Coherent vapor pockets downstream of the orifice worsen emulsification efficiency. Abstract: This work investigates cavitation patterns after a cylindrical coaxial orifice at different orifice to outlet channel diameter ratios β  < 0.1. Further the influence of cavitation pattern on emulsion formation efficiency in high pressure homogenization is shown. At constant pressure loss (Δ p ) and varying β, three characteristic cavitation patterns (jet cavitation, choked cavitation and hydraulic flip) were detected via high speed imaging and acoustical measurement. The study shows that a surfactant concentration up to 10 −4  mol·L −1 and disperse phase content up to 10 wt.% do not influence cavitation pattern transition in the investigated fluid. Emulsification results indicate decreasing emulsification efficiency with increasing β and thereby a strong correlation to the detected cavitation patterns.